In vitro and in vivo pharmacodynamics of three novel antileishmanial lead series. Issue 1 (April 2018) - Van den Kerkhof, M.; Mabille, D.; Chatelain, E.; Mowbray, C.E.; Braillard, S.; Hendrickx, S.; Maes, L.; Caljon, G.
Abstract: Objectives: Three new chemical series (bicyclic nitroimidazoles, aminopyrazoles and oxaboroles) were selected by Drugs for Neglected Diseases initiative as potential new drug leads for leishmaniasis. Pharmacodynamics studies included both in vitro and in vivo efficacy, cross-resistance profiling against the current antileishmanial reference drugs and evaluation of their cidal activity potential. Methods: Efficacy against the reference laboratory strains of Leishmania infantum (MHOM/MA(BE)/67/ITMAP263) and L. donovani (MHOM/ET/67/L82) was evaluated in vitro on intracellular amastigotes and in vivo in the early curative hamster model. Cidal activity was assessed over a period of 15 days in an in vitro 'time-to-kill' assay. Cross-resistance was assessed in vitro on a panel of L. infantum strains with different degrees of resistance to either antimony, miltefosine or paromomycin. Results: All lead compounds showed potent and selective in vitro activity against the Leishmania strains tested and no cross-resistance could be demonstrated against any of the current antileishmanial drugs. Cidal activity was obtained in vitro for all series within 15 days of exposure with some differences noted between L. donovani and L. infantum . When evaluated in vivo, all lead compounds showed high efficacy and no adverse effects were observed. Conclusions: The new lead series were shown to have cidal pharmacodynamic activity. The absence of cross-resistance with any of the current antileishmanial drugs opens possibilities for combination treatment to reduce the likelihood of treatment failures and drug resistance. Graphical abstract: Image 1 Highlights: Good efficacy was evaluated for all series in vitro and in vivo. No cross-resistance towards current anti-leishmanial drugs was observed. Cidal activity was obtained in vitro for all series within 15 days of exposure. Some differences were observed between L. infantum and L. donovani.